2007
DOI: 10.1177/1365480207073702
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing student voice: values and perspectives

Abstract: This article explores some of the core values which underpin student voice work. We are in the very early stages of trying to understand the values that surround student voice and hope to develop these understandings by drawing on the work of various educational theorists. Throughout the article we examine some of the complexities that arise in theorizing student voice, and allude to the practical implications of the values in the context of student voice work in schools and the implications to school improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
149
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 18 publications
0
149
0
9
Order By: Relevance
“…Student co-creation allows for stakeholders to listen and to take into account the students' voice in terms of their opinions or feelings about their institutional experience. Nowadays, this fact is a core value in an HE inclusive system [44]. Although several approaches and criteria have been already provided by scholars in an HE context, there is still lack of consensus on how to implement co-creation processes [45][46][47][48].…”
Section: The Connection Between Hesd and Co-creationmentioning
confidence: 99%
See 1 more Smart Citation
“…Student co-creation allows for stakeholders to listen and to take into account the students' voice in terms of their opinions or feelings about their institutional experience. Nowadays, this fact is a core value in an HE inclusive system [44]. Although several approaches and criteria have been already provided by scholars in an HE context, there is still lack of consensus on how to implement co-creation processes [45][46][47][48].…”
Section: The Connection Between Hesd and Co-creationmentioning
confidence: 99%
“…It is considered that an inclusive perspective, where students have a voice, co-create their own knowledge, and are involved in different university processes, increases, in this way, their skills and competences [17,44], and hence their further applicability.…”
Section: The Connection Between Hesd and Co-creationmentioning
confidence: 99%
“…Similarly, Czerniawski (2012) emphasises the existence of different forms of professional trust in different national locations. To include the other, silent and, perhaps, controversial voices is a requirement for achieving the potential of student voice work that can increase social justice (Robinson and Taylor, 2007). This is particularly relevant to the research involving student voice in African contexts where inequality and marginalization in education are critical issues.…”
Section: Potential Of Student Voice For Educational Changementioning
confidence: 99%
“…However, they reported that as private candidates they did not receive equal treatment in the national exams. To include these silent and, perhaps, controversial voices is a requirement for achieving the potential of student voice work that can increase social justice (Robinson and Taylor 2007;Warrington and Kiragu 2012). This issue is particularly relevant to this research involving the voices of female students in Sub-Saharan African contexts where inequality and marginalisation in education are critical issues, particularly in post-primary education.…”
Section: Towards Transformative Student Voice Work In Secondary Educamentioning
confidence: 99%
“…This has the effect of sustaining existing hierarchies. Sometimes student voice is assumed to be 'monolingual' (Robinson and Taylor 2007), denying the multi-faceted nature of student perspectives (Rubin and Silva 2003). In particular, students who speak in the language of the dominant discourses of a school, with 'the voice of the subaltern' (Spivak in Morton 2003), are more likely to be heard than those with dissonant voices or who use a different register from that of the dominant discourses (Barton and Tusting 2005).…”
Section: Discourses Of Empowerment and Discipline: Studentsmentioning
confidence: 99%